Evaluating testing practice between automated and manual test: a case study in Openet Telecom Malaysia / Nora Muhammad Abdul Ghani - Muhammad Abdul Ghani, Nora (2013)
This study basically to evaluate the testing practice that currently implement in Openet Telecom Malaysia. At the moment, Openet apply Manual and Automated test in their projects. As far as we concern, Automated testing have many advantages over Manual testing. However, not all projects can use Automated testing. At some point Manual testing still significant to apply since it more suitable to implement compare with Automated testing in certain scenario. Thus, this study will identified which type of testing should be implementing in Openet project. This study will focus on Transaction Management (TM) project and Policy Management (PM) project. The objectives of this study are to gather requirement for Openet project between automated and manual test using Black Box testing technique, to analyse the testing practice implement in Openet for Transaction Management (TM) and Policy Management (PM) project and to propose recommendation of testing practice that suitable for Openet's project scope. Therefore, this study will identify the suitable testing practice in Openet project in order to give good test result as overall whether to implement Automated testing, Manual testing or both testing simultaneously in Transaction Management (TM) project and Policy Management (PM) project.